2022
DOI: 10.2196/35466
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perspectives on Their Relationship With Their Adolescent Children With Internet Addiction: Survey Study

Abstract: Background Parents of adolescents with internet addiction are confronted with their children’s internet problems on a daily basis. Parents may notice that adolescents with addiction may also have emotional and behavioral problems, including impulsivity and violence. Parenting styles have been found to be related to internet addiction. Objective The purpose of this study is to investigate parents’ perspectives on their parenting style, relationship with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…At present, scholars' studies on the prevention and control of juvenile digital addiction primarily focus on the subjects of families, schools, communities, experts, libraries, children's homes, other fields, cultural service institutions, and game platforms. Relatively comprehensive and scientific suggestions have been put forward for the intervention of digital addiction for minors, involving information literacy, mental health, social entertainment, value realisation, and other aspects (Docharkhehsaz et al,2022;Horita et al,2022;Fan,2022).…”
Section: Regulation and Guidance Of Digital Addictionmentioning
confidence: 99%
“…At present, scholars' studies on the prevention and control of juvenile digital addiction primarily focus on the subjects of families, schools, communities, experts, libraries, children's homes, other fields, cultural service institutions, and game platforms. Relatively comprehensive and scientific suggestions have been put forward for the intervention of digital addiction for minors, involving information literacy, mental health, social entertainment, value realisation, and other aspects (Docharkhehsaz et al,2022;Horita et al,2022;Fan,2022).…”
Section: Regulation and Guidance Of Digital Addictionmentioning
confidence: 99%
“…In addition, parental perception and regulation of youth internet activities have been identified as important correlates of youth internet behavior . Parent perceptions of family interactions, including parenting and sibling relationships, have previously been linked to child and adolescent PIU in Chinese and Japanese populations, but to our knowledge, similar research has not been undertaken in a large sample of US families. Families with a higher negative perception of the internet were most likely to have intergenerational conflict …”
Section: Introductionmentioning
confidence: 96%
“…Empirical evidence has illuminated the significant impact of children’s electronic media use on the quality of this relationship. Studies such as those by Zhu et al, Horita et al, and Ahmadian et al have consistently shown that higher levels of problematic internet use among children are linked to poorer parent–child relationships [ 30 , 31 , 32 ]. The Displacement Hypothesis posits that excessive use of electronic media may supplant meaningful face-to-face interactions, eroding intimacy and satisfaction within familial relationships [ 33 ].…”
Section: Introductionmentioning
confidence: 99%